Catalytic Hydrogenation of N-Benzylideneaniline Using a New Complex of Ruthenium(Ii) Derived from 2-Ferrocenyl-1,8-Naphthyridine - Moya-Duran, S; Moya-Duran, S (2011)
2-Ferrocenyl-1,8-naphthyridine (1) and cis,cis,cis-dicarbonyl-dichloro-bis (2-ferrocenyl-1,8-naphthyridine) ruthenium(II) complex (2) have been synthesized and characterized by IR, 1H-NMR spectroscopy and elemental analysis. The structure of the compounds was determined by X-ray analysis. The complex (2) showed catalytic activity in the hydrogenation reaction of N-benzylideneaniline by hydrogen transfer with conversions between 89% and 33% for catalyst/substrate relations 200/1 and 400/1. © 2011 Elsevier B.V.